2016
DOI: 10.1007/s00264-016-3124-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the early efficacies of autologous bone grafting and interbody fusion cages for treating degenerative lumbar instability in patients of different ages

Abstract: At different ages, the interbody fusion cages can better preserve the intervertebral space and the intervertebral foramen height. However, autologous bone graft can rapidly achieve a bony fusion. Interbody fusion cages are therefore ideal for young adults, while autologous bone grafting is ideal for middle-aged and elderly patients who receive a modified TLIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[ 1 , 2 ] Deng et al [ 3 ] indicated that cages could promote effective clinical and radiographic outcomes when used for degenerative lumbar diseases. Zhong et al [ 4 ] found that the interbody fusion cages can better preserve the intervertebral space and the foramen height than the autologous bone graft. However, intraoperative and postoperative complications are still encountered, as cage migration into the adjacent vertebral bodies and posterior dislocation into the spinal canal are well-known complications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ] Deng et al [ 3 ] indicated that cages could promote effective clinical and radiographic outcomes when used for degenerative lumbar diseases. Zhong et al [ 4 ] found that the interbody fusion cages can better preserve the intervertebral space and the foramen height than the autologous bone graft. However, intraoperative and postoperative complications are still encountered, as cage migration into the adjacent vertebral bodies and posterior dislocation into the spinal canal are well-known complications.…”
Section: Introductionmentioning
confidence: 99%
“…For most types of bone graft procedures, autologous bone from the iliac crest has been considered the gold standard because of high bioactivity and lack of immunity reaction. It is reported that successful and rapid lumbar fusion rates with the autogenous iliac crest bone grafts have been reported higher than 90% 24,25 . However, taking too many autogenic bones will definitely lead to donor site morbidity and insufficiency of local bone will lead to poor rate of bone union 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Intervertebral heights were measured as the average height of the anterior and posterior intervertebral space by lateral X-ray before the surgery, 2 weeks after the surgery and at the last follow-up to evaluate the stability of fixation. 11,12 CT scans were taken at the last follow-up to evaluate the position of the screws and the fusion of the surgical segment.…”
Section: Discussionmentioning
confidence: 99%